Dual‐Cues Laden Scaffold Facilitates Neurovascular Regeneration and Motor Functional Recovery After Complete Spinal Cord Injury. Issue 10 (19th March 2021) - Liu, Dingyang; Shen, He; Shen, Yeyu; Long, Ge; He, Xinghui; Zhao, Yannan; Yang, Zhiquan; Dai, Jianwu; Li, Xing
Abstract: Complete transection spinal cord injury (SCI) severely disrupts the integrity of both neural circuits and the microvasculature system. Hence, fabricating a functional bio‐scaffold that could coordinate axonal regeneration and vascular reconstruction in the lesion area may emerge as a new paradigm for complete SCI repair. In this study, a photosensitive hydrogel scaffold loaded with collagen‐binding stromal cell‐derived factor‐1a and Taxol liposomes is capable of inducing migration of endothelial cells and promoting neurite outgrowth of neurons in vitro. In addition, when implanted into a rat T8 complete transection SCI model, the above dual‐cues laden scaffold exhibits a synergistic effect on facilitating axon and vessel regeneration in the lesion area within 10 days after injury. Moreover, long‐term therapeutic effects are also observed after dual‐cues laden scaffold implantation, including revascularization, descending and propriospinal axonal regeneration, fibrotic scar reduction, electrophysiological recovery, and motor function improvement. In summary, the dual‐cues laden scaffold has good clinical application potential for patients with severe SCI. Abstract : A dual‐cues laden hydrogel scaffold is able to synergistically promote vascular reformation and axon regeneration in the lesion epicenter post complete spinal cord injury (SCI). Moreover, implantation of the dual‐cues laden scaffold could also effectively reduce chondroitin sulfate proteoglycans and fibronectin deposition in the lesion area and improve locomotor function of hind‐limbs, which would be a promising treatment for complete SCI repair.